2003
DOI: 10.1111/j.1365-2621.2003.tb05755.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability, Structure, and Physical Characteristics of Microcapsules Formed by Spray Drying of Fish Oil with Protein and Dextrin Wall Materials

Abstract: Maltodextrins and a highly branched cyclic dextrin (HBCD) were tested for their ability to serve as wall materials for microcapsules with proteins. HBCD or a maltodextrin of DE18 with sodium caseinate (SC) improved the oxidative stability of encapsulated fish oil; however, the DE18/SC wall system had 2 disadvantages: browning induced by the Maillard reaction and agglomeration. The oil load level and the selection of dextrin strongly affected the outer topography and the inner structure, as well as the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(131 citation statements)
references
References 22 publications
5
121
0
5
Order By: Relevance
“…Formulations containing WPC80 and sucrose had higher encapsulation efficiencies than those containing WPC80/DE24. The higher encapsulation efficiency of powders formulated with WPC80 and sucrose compared to that of the WPC80/DE24 powders is in line with the observations of others who obtained a higher encapsulation efficiency in spray-dried emulsions stabilised by NaCas in combination with the increased dextrose equivalent of the carbohydrates [13,16].…”
Section: Milk Constituents For Microencapsulation Of Oilssupporting
confidence: 91%
“…Formulations containing WPC80 and sucrose had higher encapsulation efficiencies than those containing WPC80/DE24. The higher encapsulation efficiency of powders formulated with WPC80 and sucrose compared to that of the WPC80/DE24 powders is in line with the observations of others who obtained a higher encapsulation efficiency in spray-dried emulsions stabilised by NaCas in combination with the increased dextrose equivalent of the carbohydrates [13,16].…”
Section: Milk Constituents For Microencapsulation Of Oilssupporting
confidence: 91%
“…Recently, n-OSA starch has been permitted for use as an additive for formulae and weaning foods for infants and young children in the EU [12]. Studies on the oxidative stability of microencapsulated oils rich in LC-PUFA, like fish oil, with sodium caseinate, dextrins and highly branched cyclic dextrins or modified cellulose are available [13,14], but studies on the oxidative stability of microencapsulated oils with n-OSA starch are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, maltodextrin, a digestion product of starch, is just composed of D -glucose units [39]. In addition, increase in dextrose equivalent (DE) of carbohydrates has protective effect against oxidation [36]. This is because EE increases, as DE values of carbohydrates increase.…”
Section: Spray Dryingmentioning
confidence: 99%
“…As mentioned before, carbohydrates, proteins or combination of these are generally used as wall materials for oil encapsulation. The major functions of carbohydrates in encapsulation are promotion of drying properties of wall matrix by increasing dry crust formation over the drying droplets [36]. Minemoto et al [37] found that the emulsions prepared with gum arabic is more stable than the emulsions with maltodextrin.…”
Section: Spray Dryingmentioning
confidence: 99%